2021
DOI: 10.1016/j.wjorl.2020.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Presentation and outcomes of chronic rhinosinusitis following liver and kidney transplant

Abstract: Objective This study aims to describe presenting characteristics of patients diagnosed with non-invasive chronic rhinosinusitis (CRS) following liver or kidney transplant and determine factors associated with disease-related complications, selection of endoscopic sinus surgery (ESS), and disease resolution in this population. Study design Retrospective chart review. Setting An academic tertiary care center (Mayo Clinic, Rochester, Minnesota).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
(52 reference statements)
4
4
0
Order By: Relevance
“…Some studies suggest that certain combinations of immunosuppressive therapy and low-dose prednisone may actually be protective for rhinologic disease. 7,15,16 Our findings are consistent with the majority of studies, as we noted that the certain immunosuppressant drugs appear to be a factor associated with recalcitrant disease. 3,7,10,24,25…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some studies suggest that certain combinations of immunosuppressive therapy and low-dose prednisone may actually be protective for rhinologic disease. 7,15,16 Our findings are consistent with the majority of studies, as we noted that the certain immunosuppressant drugs appear to be a factor associated with recalcitrant disease. 3,7,10,24,25…”
Section: Discussionsupporting
confidence: 91%
“…The frequency of ESS in solid transplant recipients in our study was 36% which coincides with estimates described in the literature. 15 Based on our results as well as other smaller studies, CRS patients with liver transplants were consistently documented as having recalcitrant CRS. 15 In fact, our univariate analysis found that patients with liver transplants had a higher risk of developing recalcitrant CRS and requiring surgery compared to all other solid organ transplant patients.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…None of the 10 patients diagnosed with sinusitis or neoplasm in the screening had a complicated course after HTx. Similar observations have been reported in literature: in a cohort of liver and kidney transplant recipients no complicated sinusitis was witnessed [17], and the presence of pretransplant chronic rhinosinusitis does not contribute to mortality after liver transplant [18].…”
Section: Post-transplant Evaluationsupporting
confidence: 89%
“…In our study, chronic hepatitis was detected in 1 case (9.1%), chronic glomerulonephritis -in 1 case (9.1%), chronic pyelonephritis -in 1 case (9.1%). Dysfunction of these organs is accompanied by intoxication, immune disorders, which can cause the development of bacterial-fungal chronic rhinosinusitis [44].…”
Section: Discussionmentioning
confidence: 99%